Continuous synthesis of carbon dots with full spectrum fluorescence and the mechanism of their multiple color emission. Issue 23 (29th October 2019) - Shao, Meng; Yu, Qin; Jing, Nan; Cheng, Yu; Wang, Dong; Wang, Yun-Dong; Xu, Jian-Hong
Abstract : Continuous synthesis of carbon dots with full-spectrum fluorescence and the mechanism of their multiple color emission and applications. Abstract : Carbon dots with different emission fluorescence have a great number of potential applications for various areas from in vitro imaging and biotherapy, due to the good biosafety of red fluorescent CDs, to efficient ion detection and photocatalysis, due to the excellent photoluminescence properties of blue fluorescent carbon dots. Traditional methods for the synthesis of full-spectrum carbon dots require 24 h of synthesis and complex column chromatography. In this paper, a facile and efficient microfluidic method to continuously synthesize small and uniform carbon dots with full-spectrum emission fluorescence is developed for the first time. The synthesis process could be reduced to 20 minutes. Through XPS analysis and DFT calculations, it is quantitatively revealed that the number of primary amino groups determines the energy gap of the carbon dots and thus determines the fluorescence emission wavelength of the carbon dots. Applications for precise Fe 3+ detection and in vitro bio-imaging were successfully implemented, showing great potential application value of the carbon dots.